Developing consumer-based service brand equity (CBSBE): An airline industry perspective / Md Moniruzzaman Sarker - Md Moniruzzaman , Sarker (2020)
The competitive challenges facing airline companies such as consolidation, merger, acquisition and passengers’ dynamic buying behaviour require sound branding strategies that may help organisations survive and thrive effectively. Although contemporary brand equity models have been acknowledged and tested in the service branding context, they are not quite adaptable to the airline sector. A critical review of the literature also confirms that earlier models are more appropriate for product-dominant brands, as they ignore the crucial roles of direct service experience, which is the nucleus of service organisations. Besides, the two essential elements of brand asset (i.e., brand consistency and perceived value) are disregarded in previous service branding model. Therefore, using airline service as the basis, this research aims at proposing and examining an alternative service branding theory known as consumer-based service brand equity (CBSBE) model which takes into consideration the direct service experience, brand consistency and perceived value along with existing components such as brand awareness, brand meaning and brand equity. Using the survey research methodology, data were collected via a structured questionnaire, through: 1) airport intercept from international airline passengers in Kuala Lumpur International Airport (KLIA); and 2) online platforms such as WhatsApp, WeChat, Facebook messenger and email. A total of 652 usable responses were gathered and analysed. Using the partial least squares structural equation modelling (PLS-SEM) techniques, the results indicate that airline service direct experience and brand consistency are highly important aspects for strengthening brand equity components of services. Subsequently, maximizing perceived value, followed by creating favourable brand meaning are the nucleus of branding services. The rather feeble influence of brand awareness in creating positive SBE may suggest that consumer experience-based assessment through perceived value and brand meaning is more powerful than brand awareness in eliciting a positive differential response of SBE. Overall, the theoretical conceptualisation and empirical evidences of this study affirm that the proposed CBSBE model is valid in explaining branding strategy of the airline industry. The research yields theoretical, methodological and practical implications. From a theoretical standpoint, the inclusion of brand consistency and perceived value in suggesting an alternative service branding framework called the CBSBE model enhances the depth of service branding theory. Theoretically, building an airline brand depends very much on high perceived value and favourable brand meaning, which are invincibly materialised by airline service direct experience and brand consistency. Also, the adoption of quantitative methods in operationalising the model in airline service setting provides some methodological contributions. As a higher-order formative construct, airline service direct experience offers a comprehensive understanding by integrating five essential dimensions - in-flight-core service, employee service, interaction with other passengers, purchase decision experience and airport service experience. The study further argues that the generalisability of the CBSBE model would be achieved if direct service experience components are tailored to a specific service setting. Finally, for the airline brand/marketing manager, this research offers crucial insights in designing airline branding strategy. In-flight-core service and employee service are the most critical aspects of airline service; whereas airport service experience, interaction with other passengers and purchase decision experience are the integral parts of airline service direct experience. Thus, maximising value, creating favourable meaning and managing consistency in delivering an enjoyable airline service (i.e., brand consistency) through direct service encounters will mitigate managerial and marketing difficulties when building a strong airline brand.